Faktor-Faktor Yang Berhubungan Dengan Status Gizi Pada Anak Usia Sekolah di SD 4 Penebel - Ariawan, I Gede Nova; Prihayanti, Ni Komang Trisna; Purnama, Pande Made Dwi Ayu; Susanti, Ida Ayu; Dharmayanti, Ni Made Sri; Diastuti, Ni Nyoman Parayoni; Devi, Ni Luh Putu Shinta (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2021)
Nutritional status is a crucial indicator in developing human resources. Nutritional status indicates theexisting of stability between nutrition intake and requirements amount of the body for compliance ofvarious body functions which is affected by several factors. The aim of the study is investigated factors thatcorrelate to nutritional status among school-age children at SD 4 Penebel. This study used cross-sectionaldescriptive correlation design with total participants of 75 students who enrolled in this study anddetermined by using total sampling. Demographic questionnaire and observational sheet of anthropometrymeasurement used as instruments in collecting data. The results showed that there were no significantfactors that associated with nutritional status among school-age children at SD 4 Penebel, such as age (p =0,178), sex (p = 0,404), maternal education (p = 0,444), maternal occupation (p = 0,095), number ofsiblings (p = 0,121), anthelmintic consumed status (p = 0,361), and health status (p = 1,000). Thisresearch conducted for government program improvement that focused on nutrition issue, moreover itshould be developed with a better research method.